DEVELOPMENT AND ANALYSIS OF RF RECTIFIER CIRCUIT DESIGN FOR WIRELESS BATTERY CHARGING - DORAISELVAN, LOGARAAJ (IRC, 2019)
This paper discusses on optimising the RF rectifier circuit that is suitable for wireless battery charging. The initial stage of a rectifier circuit comes from a voltage multiplier and it converts low AC power to high DC power. The rectifier helps in converting AC to DC and there are two type of rectifier which are half-wave rectifier and full-wave rectifier. This paper works on full-wave rectifier circuit and a little knowledge of Heinrich Greinacher Villard course. The current design of rectifier DC conversion efficiency about 50%. This low-level power maybe caused by the level of RF energy and the mismatching of the antenna to the rectifier. To further enhance the rectifier circuit, the design or the matching impedance circuit is changed since the T-model matching circuit is used. The idea of using this model because it helps in increasing the power efficiency of the circuit. The target efficiency for this project is at least 70%. The efficiency of the output power is not only affected by the rectifier circuit, but it is also affected by the antenna. The rectifier plays an important role as compared to the antenna.